Influence of carbohydrate ingestion on cytokine responses following acute resistance exercise - Chan, M. A.; Koch, A. J.; Benedict, S. H.; Potteiger, (International Journal of Sport Nutrition and Exercise Metabolism, 2003)
The effect of carbohydrate supplementation (CHO) on interleukin 2 (IL-2) and interleukin 5 (IL-5) secretion following acute resistance exercise was examined in 9 resistance-trained males. Subjects completed a randomized, double-blind protocol with exercise separated by 14 days. The exercise consisted of a high intensity, short rest interval squat workout. Subjects consumed 1.0 g · kg body mass-1 CHO or an equal volume of placebo (PLC) 10 min prior to and 10 min following exercise. Blood was collected at rest (REST), immediately post exercise (POST), and at 1.5 h of recovery (1.5 h POST). Isolated peripheral blood mononuclear cells were stimulated with PHA and assayed for IL-2 and IL-5 secretion. IL-2 secretion was significantly decreased at POST for both the PLC and CHO groups. However, the degree of decrease was less in the CHO group (16%) than in the PLC group (48%), and this difference was statistically significant. These responses were transient, and the values returned to normal by 1.5 h POST. A mild and transient but significant decrease in IL-5 secretion by the PLC group was observed at POST (26%) compared to REST. No significant decrease was observed in IL-5 secretion for CHO from REST to POST (12%). These data support a possible effect of carbohydrate supplementation on IL-2 and IL-5 secretion following high-intensity resistance exercise.